There Will Be More d’Edward Bond : pour un autre théâtre politique - Eléonore Obis (Sillages Critiques)
My contention in this article is that Edward Bond’s vision of political theatre is both illustrated and renewed by  one of his latest plays, There Will Be More (2010), which is still not published and is supposed to be the first part of a new trilogy. The play is a rewriting of the tragedy of Medea and displays all the techniques and dramatic strategies developed by Bond over the years since Saved. However, it seems some elements of rupture can also be observed, and these could be interpreted as a significant renewal of Bond’s political theatre.